The Mejillonia suspect terrane (Northern Chile): Late Triassic fast burial and metamorphism of sediments in a magmatic arc environment extending into the Early Jurassic - Casquet , C. (2014)
The Mejillonia terrane, named after the Mejillones Peninsula (northern Chile), has been traditionally considered an early Paleozoic block of metamorphic and igneous rocks displaced along the northern Andean margin in the Mesozoic. However, U–Pb SHRIMP zircon dating of metasedimentary and igneous rocks shows that the sedimentary protoliths were Triassic, and that metamorphism and magmatism took place in the Late Triassic (Norian). Field evidence combined with zircon dating (detrital and metamorphic) further suggests that the sedimentary protoliths were buried, deformed (foliated and folded) and metamorphosed very rapidly, probably within few million years, at ca. 210 Ma. The metasedimentary wedge was then uplifted and intruded by a late arc-related tonalite body (Morro Mejillones) at 208 ± 2 Ma, only a short time after the peak of metamorphism. The Mejillones metamorphic and igneous basement represents an accretionary wedge or marginal basin that underwent contractional deformation and metamorphism at the end of a Late Permian to Late Triassic anorogenic episode that is well known in Chile and Argentina. Renewal of subduction along the pre-Andean continental margin in the Late Triassic and the development of new subduction-related magmatism are probably represented by the Early Jurassic Bólfin–Punta Tetas magmatic arc in the southern part of the peninsula, for which an age of 184 ± 1 Ma was determined. We suggest retaining the classification of Mejillonia as a tectonostratigraphic terrane, albeit in this new context.